A Comprehensive Review of Renewable and Sustainable Energy Sources with Solar Photovoltaic Electricity Advancement in Bangladesh - Hussain, Md. Naeem; Zaman, Md Rakibur; Halim, Md Abdul; Ali, Md. Sumon; Khan, Md. Yakub Ali (Control Systems and Optimization Letters, 2024)
With an emphasis on Bangladesh's accomplishments in solar photovoltaic power production, this extensive study offers a comprehensive review of sustainable and renewable energy sources. Bangladesh, a heavily populated country that depends heavily on energy, has a difficult time satisfying its rising electrical demand while also taking environmental issues into account. The assessment covers a wide range of topics related to renewable energy sources, including solar photovoltaic technology, how it fits into the nation's current energy infrastructure, legislative frameworks, and socioeconomic effects. The report emphasizes how solar photovoltaic power may play a key role in Bangladesh's sustainable energy future by lowering the country's reliance on fossil fuels, lessening the effects of climate change, and promoting economic development via the use of renewable energy sources. This comprehensive review explores the many facets of sustainable and renewable energy sources in further detail, with a particular emphasis on Bangladesh's ever-changing solar photovoltaic power market. The topic of discussion includes developments in solar panel technology, such as increased efficiency, lower costs, and novel ideas. It also looks at how solar energy may be integrated into the current energy system, discussing the benefits and problems related to energy storage and grid modernization. This paper has the potential to improve energy security, the environment, the economy, and the general well-being of the populace, with a focus on solar PV advancement in Bangladesh. It can act as a guide for decision-makers in government, academia, and business to work together to create a more resilient and sustainable energy future for the nation. The research explores how the expansion of the solar business might lead to the creation of jobs, the improvement of skills, and the enhancement of local economies. It also takes into account the advantages for the environment that come from using less fossil fuels, such as lower greenhouse gas emissions and better air quality. This thorough review highlights the importance of Bangladesh's progress toward solar photovoltaic electricity development as a way to guarantee a sustainable and environmentally conscious energy future, lower consumer energy costs, and improve energy security in a country with rising energy consumption and aggressive renewable energy targets.